Publication productivity and citation analysis of the Medical Journal of Malaysia: 2004–2008 - Sanni, S.A.; Zainab, Awang Ngah (Malaysian Medical Association, 2012)
We analysed 580 articles (original articles only) published in Medical Journal of Malaysia between 2004 and 2008, the resources referenced by the articles and the citations and impact received. Our aim was to examine article and author productivity, the age of references used and impact of the journal. Publication data was obtained from MyAIS database and Google Scholar provided the citation data. From the 580 articles analyzed, contributors mainly come from the hospitals, universities and clinics. Contributions from foreign authors are low. The useful lives of references cited were between 3 to 11 years. ISI derived Impact factor for MJM ranged between 0.378 to 0.616. Journal self-citation is low. Out of the 580 sampled articles, 76.8% have been cited at least once over the 5 years and the ratio of total publications to citations is 1: 2.6.